The influence of different intensity of monsoon on typhoon precipitation: a comparative study of typhoons Soudelor and Maria - Zeng, Zi; Xu, Jianjun; Ye, Guiling; Shen, Wenqi (Frontiers in Earth Science, 2023)
In this paper, multiple sets of reanalysis datasets are used to analyze the intensity of the Asian summer monsoon from 1979 to 2021. Typhoon Soudelor (No. 1513) and Typhoon Maria (No. 1808) were selected from the weak monsoon year 2015 and the strong monsoon year 2018, both of which were generated in the Northwest Pacific in July and made landfall in South China. The Weather Research and Forecasting Model (WRF) was used to simulate the two typhoons, starting 48 h prior to their landfall. The reasons for the differences in precipitation and how the monsoon affects typhoon precipitation in this process are analyzed from the aspects of monsoon background, ambient weather systems, typhoon thermodynamic structure, and water vapor conditions. The analysis shows that the circulation of Soudelor was stable and maintained for a long time. Despite existing in the background of a weak monsoon, the monsoon flow was able to reach the key area affecting typhoons and inject enough warm and moist flow to affect Soudelor. Combined with the analysis of typhoon structure, the strong water vapor transport of Soudelor and increased low-level convergence were conducive to the formation of typhoon-related rainstorms. The monsoon appeared to provide environmental conditions favorable for typhoon precipitation, resulting in a wide range of precipitation and heavy precipitation. Typhoon Maria developed and changed rapidly, moved rapidly, and the precipitation maintained itself for a relatively short time. The monsoon flow was not transported into Maria, resulting in insufficient water vapor inside Maria, which prevented the strengthening of typhoon precipitation. The precipitation of Maria mainly came from the dynamics of the typhoon itself and was not affected by the monsoon. In addition, this study defines an area on the southwest side of the typhoon moving with the center of the typhoon as the key area affecting typhoons. The characteristics of this area can be simply linked to typhoon precipitation, which can be considered an important research area for future analysis and prediction of typhoon precipitation.